Methods of coping with stress and its relationship to empathy A field study on a sample of kindergarten teachers in Lattakia Governorate - سعيد, غيداء; ليلى الشريف; وفيقة علي (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of the current research is to study the levels of empathy and methods of coping with stress among kindergarten teachers, and the relationship between them, and to test the differences in empathy and methods of coping with stress according to the variable number of years of experience. A sample of (100) teachers was selected from private kindergartens in the cities of Lattakia and Jableh. The Empathy Scale prepared by Steckal (Steckal, 1994), translated by the researcher, and d scale. Abdullah Muhammad Al-Tariqa as part of his doctoral thesis at Damascus University in (2010 - 2011) for methods of coping with pressures, and the researcher followed the descriptive analytical approach. The results indicated the presence of an average level of empathy and methods of coping with pressures among kindergarten teachers, and the existence of a positive, statistically significant correlation between empathy and methods of coping with stress, and Methods of coping with stress significant differences in empathy and psychological burnout due to the variable number of years of experience.